2023
DOI: 10.3390/biom13111598
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins: Molecular Aspects on Their Neuroprotective Activity

César A. Zaa,
Álvaro J. Marcelo,
Zhiqiang An
et al.

Abstract: Anthocyanins are a type of flavonoids that give plants and fruits their vibrant colors. They are known for their potent antioxidant properties and have been linked to various health benefits. Upon consumption, anthocyanins are quickly absorbed and can penetrate the blood–brain barrier (BBB). Research based on population studies suggests that including anthocyanin-rich sources in the diet lower the risk of neurodegenerative diseases. Anthocyanins exhibit neuroprotective effects that could potentially alleviate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 157 publications
0
10
0
Order By: Relevance
“…Additionally, they show neuroprotective effects, supporting cognitive function and reducing neurodegenerative disease risk. (Za et al, 2023) In vitro and animal studies reveal anthocyanins' anti-cancer properties by inhibiting cancer cell growth and inducing apoptosis (programmed cell death). (Lin et al, 2017;Jiang et al, 2014) Anthocyanins, implicated in blood sugar regulation and enhanced insulin sensitivity, show potential benefits for diabetes management.…”
Section: Results and Discussion Of Phytochemical Screeningmentioning
confidence: 99%
“…Additionally, they show neuroprotective effects, supporting cognitive function and reducing neurodegenerative disease risk. (Za et al, 2023) In vitro and animal studies reveal anthocyanins' anti-cancer properties by inhibiting cancer cell growth and inducing apoptosis (programmed cell death). (Lin et al, 2017;Jiang et al, 2014) Anthocyanins, implicated in blood sugar regulation and enhanced insulin sensitivity, show potential benefits for diabetes management.…”
Section: Results and Discussion Of Phytochemical Screeningmentioning
confidence: 99%
“…As mentioned above, anthocyanins have been widely studied because they are bioactive substances with many attractive characteristics (antioxidant, anti-inflammatory, antibacterial, and even anticancer properties). Indeed, consuming foods high in flavonoids (of which anthocyanins are a subgroup) has multiple health benefits, such as improvements in the cardiovascular system [ 105 ], neuroprotective effects [ 106 ], and improvement in skin texture due to their antioxidant and anti-inflammatory properties [ 107 , 108 ]. According to this, the food industry is one of the most important areas for anthocyanin application.…”
Section: Anthocyanin-based Polymers For Food Applicationsmentioning
confidence: 99%
“…It acts as an antioxidant and anti-inflammatory agent, contributing to the prevention of various diseases [78]. Additionally, anthocyanins, another type of flavonoid present in red fruits, can penetrate the blood-brain barrier and offer potential neuroprotective benefits [79]. Bortolini et al found that concentrations of 20 ug/mL of blackberry, black raspberry, blueberry, cranberry, red raspberry, and strawberry extracts were effective in preserving the cellular viability of bv-2 microglia when exposed to oxidative stress [3].…”
Section: Cranberry (Vaccinium Oxycoccos)mentioning
confidence: 99%